Systematic Review of Methods for Individual Prediction of Postoperative Pain - Krister Mogianos; Jonas Åkeson; Anna K. M. Persson (Pain Research and Management)
Conclusion: Various screening methods have been proposed to identify patients prone to postoperative pain. The focus has shifted from procedure-specific to individualized strategies to improve early management of pain. However, many traditional predictive methods still have a questionable role in clinical practice.